PENGEMBANGAN ASESMEN DIGITAL DALAM PEMBELAJARAN PAI - Eliva Sukma Cipta; Siti Asiah Nurfadillah; Asep Muhammad Irfan Hilmi; Iis Mulyani; Muhammad Endang Szafei (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Industrial Revolution 4.0 has driven significant transformation in educational assessment, including in Islamic Religious Education (PAI). Conventional assessments are often episodic, narrow, and fail to capture affective and spiritual domains. This study aims to analyze the implementation and implications of digital assessment in PAI learning through a field research approach. The research employs a qualitative descriptive approach with direct observations, interviews, and documentation at SMAN 1 Cicalengka. The research subject was one PAI teacher and students in grades X-XII. Data collection techniques included classroom observation, teacher interviews, and analysis of assessment documents. The results indicate that digital assessment through Google Forms and Quizizz has been successfully implemented, offering advantages such as efficiency, real-time feedback, increased student engagement, and ease of grade recording. However, challenges include internet connectivity issues, limited student data quotas, and maintaining student focus during digital assessments. The implications are that digital assessment can strengthen learning effectiveness when designed with proper pedagogical support and infrastructure readiness. The novelty lies in combining theoretical understanding with practical field implementation of digital assessment in Indonesian Islamic Education contexts. This study recommends strengthening infrastructure support, providing continuous teacher training, and developing monitoring strategies to ensure optimal implementation of digital assessments.   Keywords: Digital assessment, Islamic Religious Education, field research, learning evaluation, educational technology   ABSTRAK Revolusi Industri 4.0 telah mendorong transformasi signifikan dalam asesmen pendidikan, termasuk dalam pembelajaran Pendidikan Agama Islam (PAI). Asesmen konvensional cenderung bersifat episodik, sempit, dan kurang menjangkau ranah afektif serta spiritual. Penelitian ini bertujuan menganalisis implementasi dan implikasi asesmen digital dalam pembelajaran PAI melalui pendekatan penelitian lapangan. Penelitian menggunakan pendekatan kualitatif deskriptif dengan observasi langsung, wawancara, dan dokumentasi di SMAN 1 Cicalengka. Subjek penelitian adalah satu guru PAI dan siswa kelas X-XII. Teknik pengumpulan data meliputi observasi pembelajaran, wawancara guru, dan analisis dokumen asesmen. Hasil penelitian menunjukkan bahwa asesmen digital melalui Google Forms dan Quizizz telah berhasil diimplementasikan, menawarkan keunggulan efisiensi, umpan balik real-time, peningkatan keterlibatan siswa, dan kemudahan pencatatan nilai. Namun, tantangan yang dihadapi meliputi ketidakstabilan koneksi internet, keterbatasan kuota data siswa, dan pemeliharaan fokus siswa selama asesmen digital berlangsung. Implikasinya, asesmen digital dapat memperkuat efektivitas pembelajaran ketika dirancang dengan dukungan pedagogis yang tepat dan kesiapan infrastruktur yang memadai. Kebaruan penelitian ini terletak pada penggabungan pemahaman teoretis dengan implementasi praktis lapangan asesmen digital dalam konteks Pendidikan Agama Islam Indonesia. Penelitian ini merekomendasikan penguatan dukungan infrastruktur, pemberian pelatihan berkelanjutan bagi guru, dan pengembangan strategi pengawasan untuk memastikan implementasi asesmen digital yang optimal.   Kata Kunci: Asesmen digital, Pendidikan Agama Islam, penelitian lapangan, evaluasi pembelajaran, teknologi pendidikan